Association Between Stent Implantation and Progression of Nontarget Lesions in a Rabbit Model of Atherosclerosis. (November 2021) - Ma, Jing; Liu, Xiaoling; Qiao, Lei; Meng, Linlin; Xu, Xingli; Xue, Fei; Cheng, Cheng; Han, Ziqi; Lu, Yue; Zhang, Wencheng; Bu, Peili; Zhang, Meng; et al.
Abstract : Background: Progression of nontarget lesions (NTLs) after percutaneous coronary intervention (PCI) has been reported. However, it remains unknown whether progression of NTLs was causally related to stenting. This study was undertaken to test the hypothesis that stent implantation triggers acute phase response and systemic inflammation which may be associated with progression of NTLs. Methods: Thirty New Zealand rabbits receiving endothelial denudation and atherogenic diet were randomly divided into stenting, sham, and control groups. Angiography and intravascular ultrasonography were performed in the stenting and sham groups, and stent implantation performed only in the stenting group. Histopathologic study was conducted and serum levels of APPs (acute phase proteins) measured in all rabbits. Proteomics analysis was performed to screen the potential proteins related to NTLs progression after stent implantation. The serum levels of APPs and inflammatory cytokines were measured in 147 patients undergoing coronary angiography or PCI. Results: Plaque burden in the NTLs was significantly increased 12 weeks after stent implantation in the stenting group versus sham group. Serum levels of APPs and their protein expression in NTLs were significantly increased and responsible for stenting-triggered inflammation. In patients receiving PCI, serum levels of SAA-1 (serum amyloid A protein 1), CRP (C-reactive protein), TNF (tumor necrosis factor)-α, and IL (interleukin)-6 were substantially elevated up to 1 month post-PCI. Conclusions: In a rabbit model of atherosclerosis, stent implantation triggered acute phase response and systemic inflammation, which was associated with increased plaque burden and pathological features of unstable plaque in NTLs. The potential mechanism involved vessel injury-triggered acute phase response manifested as increased serum levels of SAA-1, CRP, and LBP (lipopolysaccharide-binding protein) and their protein expression in NTLs. These findings provided a new insight into the relation between stent implantation and progression of NTLs, and further studies are warranted to clarify the detailed mechanism and clinical significance of these preliminary results. Registration: URL: http://www.chictr.org.cn ; Unique identifier: ChiCTR1900026393. Abstract : Supplemental Digital Content is available in the text.